Hydrodynamic analysis of a heave-hinge wave energy converter combined with a floating breakwater - Wei, Yujia; Yu, Shuangrui; Li, Xiang; Zhang, Chongwei; Ning, Dezhi; Huang, Luofeng (Elsevier, 2024)
Research interest in breakwater design has increased recently due to the impetus to develop marine renewable energy systems, as breakwaters can be retrofitted to harness wave energy at the same time as attenuating it. This study investigates a novel system of attaching a hinge baffle under a floating breakwater. The floating breakwater itself acts as a heaving wave energy converter, and meanwhile the hinge rotation provides a second mechanism for wave energy harnessing. A computational model with multi-body dynamics was established to study this system, and a series of simulations were conducted in various wave conditions. Both wave attenuation performance and energy conversion ratio were studied, using an interdisciplinary approach considering both coastal engineering and renewable energy. In particular, the performance of the proposed system is compared with contemporary floating breakwater designs to demonstrate its advantage. Overall, a useful simulation framework with multi-body dynamics is presented and the simulation results provide valuable insights into the design of combined wave energy and breakwater systems.
Keywords: Floating breakwater; Wave energy converter; Fluid-structure interaction; Hydrodynamics; Multi-body dynamics; OpenFOAM